Laboratory evaluation on pathogenic potentialities of Vibrio furnissii - Vera Magalhães; Adauto Castello Filho; Macelo Magalhães; Tania T. Gomes (Memorias do Instituto Oswaldo Cruz, 1993)
Sixteen strains of Vibrio furnissii recovered from 16 Brazilian patients with diarrhea were screened for virulence-associated factors. All strains were non-invasive, non-fimbriated, and did not produce either enterotoxins or cholera-like toxin. In contrast, most were hemolytic on blood agar and their broth-culture supernatants damaged HeLa cell monolayers. These cytolysins, as accepted for other enteropathogenic members of the family Vibrionaceae, might be determinants of pathogenicity in V. furnissii-mediated enteritis.